2006
DOI: 10.1111/j.1741-6612.2006.00167.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of an exercise intervention to reduce functional decline and health service utilisation in the hospitalised elderly

Abstract: Objective:  Functional decline is experienced by up to 50% of older hospitalised patients and is associated with increased institutionalisation, mortality and length of stay (LOS). We aimed to determine the effectiveness of an exercise program in reducing functional decline and health service utilisation in older inpatients. Methods:  A single‐blinded randomised controlled trial was conducted in a tertiary metropolitan hospital involving 180 acute general medical patients aged ≥ 65 years. In addition to usua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
126
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(135 citation statements)
references
References 19 publications
7
126
0
2
Order By: Relevance
“…38 Even when comparing our recruitment to exercise studies done in other older adult inpatients without a cancer diagnosis, our recruitment rate remains favorable. 18 Adherence to the exercise program was a greater challenge in this population. Only 70.8% of enrolled subjects participated in exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Even when comparing our recruitment to exercise studies done in other older adult inpatients without a cancer diagnosis, our recruitment rate remains favorable. 18 Adherence to the exercise program was a greater challenge in this population. Only 70.8% of enrolled subjects participated in exercise.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 A few studies have specifically reported the benefit of exercise during hospitalization on physical function in older non-cancer populations. 18,19 Specific to cancer patients, an increasing body of literature supports the benefit of exercise both during and after cancer treatment. [20][21][22][23][24] There is increased interest in promoting exercise early in treatment to maximize functional status during and after receipt of chemotherapy.…”
Section: Introductionmentioning
confidence: 98%
“…Thirty minutes twice daily of supervised activity has been found to provide for gains in physical function and reduced length of stay in patients aged 65 years or older [42], yet three hours per day, five days a week has been found to provide such improvement in stroke patients [43]. A further, recent study of the time use of stroke patients undergoing rehabilitation in skilled nursing facilities indicated that therapeutic time use was significantly associated with an improved functional capability [35].…”
Section: Discussionmentioning
confidence: 95%
“…Se seleccionaron estudios que evaluaran el efecto del ejercicio solo o asociado con una intervención geriátrica multidimensional, comparado con la atención convencional. Los estudios mostraron diferencias en aspectos metodológicos e intervenciones que dificultó el análisis, comparación y validez de los resultados, además solo cinco investigaciones tuvieron información sobre el estado funcional al alta (23,(51)(52)(53)(54). (51).…”
Section: Manejo De Declinación Funcionalunclassified
“…Las tres investigaciones que aplicaron intervención geriátrica multidimensional con ejercicio, obtuvieron mejores resultados funcionales durante la hospitalización comparado con la atención convencional (23,51,52) y las dos investigaciones donde solo se realizó ejercicio hubo una tendencia hacia la mejoría (53,54). Sin embargo, se requieren de más estudios con adecuado diseño metodológico para evaluar el efecto del programa de ejercicio en ancianos hospitalizados, además de describir de forma adecuada las intervenciones.…”
Section: En Las Investigaciones De Landefeld Et Alunclassified